1998
DOI: 10.1088/0031-8949/57/3/020
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of relativistic electron positron solitary waves across an ambient magnetic field

Abstract: The nonlinear electromagnetic self-interacting wave propagating across an external magnetic field through a cold electron-positron plasma is studied. The nonlinear Schrödinger equation including nonlinear effects as relativistic change of particle mass, action of the ponderomotive force and interaction with second harmonics is derived. Obtained conditions for soliton generation suggest, as a possible provenance of micropulsations, a new region in pulsar magnetosphere near the light cylinder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…They are important in astrophysical environments, such as pulsar magnetospheres and active galactic nuclei. Plasmas of this type have been studied theoretically [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. We briefly discuss some motivations for laboratory studies:…”
Section: Electron-positron Plasmasmentioning
confidence: 99%
“…They are important in astrophysical environments, such as pulsar magnetospheres and active galactic nuclei. Plasmas of this type have been studied theoretically [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. We briefly discuss some motivations for laboratory studies:…”
Section: Electron-positron Plasmasmentioning
confidence: 99%
“…Later, Saleem et al [10] showed that the electrostatic waves near upper-hybrid resonance frequency can excite (X-)mode radiation accompanied by low frequency oscillations. The dispersion relations of ordinary and extraordinary waves and their excitations are investigated when an ion cyclotron wave passes across a magnetic field in a non-relativistic hot plasma [11]. Shkarofsky [12] earlier derived general expressions for the electromagnetic dielectric tensor in a relativistic plasma.…”
Section: Introductionmentioning
confidence: 99%
“…2-4 Their nonlinear properties are currently the focus of theoretical and numerical investigations. [5][6][7][8][9][10][11][12][13][14][15][16] Studies of the electron-positron plasmas in the laboratory present substantial challenges to the experimentalists. 16 -25 The beam-plasma system is interesting in its own right.…”
Section: Introductionmentioning
confidence: 99%